Physical Environmental Barriers to Community Mobility in Older and Younger Wheelchair Users. Issue 1 (January 2015) - Harris, Frances; Yang, Hsiang-Yu; Sanford, Jon
<x xml:space="preserve">Abstract</x> For those who rely on wheeled mobility devices for many or all of their mobility needs, barriers in the physical environment can pose significant obstacles in everyday life. Current Americans With Disabilities Act Accessibility Guidelines standards do not address barriers at the level of specificity necessary to ensure accessibility for wheelchair use. This project developed a Web-based survey to capture differences in the level of difficulty of 50 barriers that persons who use wheelchairs routinely encounter in their communities. Results showed that among the 385 people who completed the survey, the most significant differences were between older and younger manual wheelchair users and suggest that Americans With Disabilities Act Accessibility Guidelines specifications should be revised to be more sensitive to the needs of older wheelchair users.